Novice and experienced hoist operators in a helicopter hoist virtual reality simulator. (2nd January 2022) - King, M; Lenser, S; Rogers, D; Carnahan, H
ABSTRACT: Virtual reality (VR) simulation training for helicopter search and rescues (SAR) hoist operators is very uncommon in comparison to the availability of pilot simulation training. SAR hoist operators control winch systems for hoisting objects or people during helicopter flight. Using a rear crew helicopter VR training simulator we sought to quantify hoist operator performance and validate this system by showing that experienced SAR hoist operators and novices hoist differently. We recruited 12 military SARs and 11 persons without hoisting experience and examined their performance in moderate wind conditions over two landscapes, ocean and land. Experienced operators were not affected by environment, completed missions faster than novices, made fewer velocity adjustments, and demonstrated better cable management. These variables can now be used as sources of feedback to train novice hoist operators. Since there were differences between performances of experienced and novice hoist operators we have established construct validity of the simulator.